Scary symptoms?: Functional magnetic resonance imaging evidence for symptom interpretation bias in pathological health anxiety - Yan, Zhimin; Bailer, Josef; Diener, Carsten (European archives of psychiatry and clinical neuroscience, 2017)
Patients with pathological health anxiety (PHA) tend to automatically interpret bodily sensations as sign of a severe illness. To elucidate the neural correlates of this cognitive bias, we applied an functional magnetic resonance imaging adaption of a body-symptom implicit association test with symptom words in patients with PHA (n = 32) in comparison to patients with depression (n = 29) and healthy participants (n = 35). On the behavioral level, patients with PHA did not significantly differ from the control groups. However, on the neural-level patients with PHA in comparison to the control groups showed hyperactivation independent of condition in bilateral amygdala, right parietal lobe, and left nucleus accumbens. Moreover, patients with PHA, again in comparison to the control groups, showed hyperactivation in bilateral posterior parietal cortex and left dorsolateral prefrontal cortex during incongruent (i.e., harmless) versus congruent (i.e., dangerous) categorizations of body symptoms. Thus, body-symptom cues seem to trigger hyperactivity in salience and emotion processing brain regions in PHA. In addition, hyperactivity in brain regions involved in cognitive control and conflict resolution during incongruent categorization emphasizes enhanced neural effort to cope with negative implicit associations to body-symptom-related information in PHA. These results suggest increased neural responding in key structures for the processing of both emotional and cognitive aspects of body-symptom information in PHA, reflecting potential neural correlates of a negative somatic symptom interpretation bias.
Gesehen am 03.04.2018